Identifikasi indikator kinerja pengelolaan desa wisata rintisan, study kasus desa wisata Karang, Trimulyo, Sleman - Ani Wijayanti; Yitno Purwoko (Journal of Tourism and Economic, 2022)
Karang tourism village is a pioneer tourism village that was just inaugurated in 2022. The management of the Karang tourism village involves various stakeholders consisting of academics, entrepreneurs, communities, association, and government. The performance of the management and development of the Karang tourism village is measured using several indicators that have an influence on the achievement of the tourism village management target. This study uses a quantitative descriptive approach. Primary data was obtained through an instrument consisting of eight performances measured by their respective indicators. The data analysis technique used is scoring and data reduction. The results showed that the measurement results of the eight management performances of Karang tourism village showed the highest value of 2.17, namely institutional performance, while the lowest value was 0.33 namely marketing performance. The performance rating of the management of the Karang tourism village has not reached very good, but it has only reached good and sufficient, this is in accordance with the category as a pioneer tourism village. Management performance that has a good rating, namely institutions, tourist attractions, and amenities. Meanwhile, management that received sufficient ratings, namely partnership, accessibility, community participation, tourism marketing, and conservation